132 Disability among injured migrants: Prospective Outcomes of Injury Study (POIS) 12-year outcomes. (20th November 2022) - Derrett, Sarah; Anglemyer, Andy; Wyeth, Emma
Abstract : Background/Aims: Studies have found migrants have higher rates of injury incidence and mortality than people born in host countries. In New Zealand (NZ), POIS found migrants had increased risk of disability 3-months post-injury compared to non-migrants (Baker W, 2019). We aim to: describe the longer-term disability outcomes (12-years post-injury) and investigate pre-injury and injury-related risk factors for longer-term disability among migrants. Methods: Our study recruited NZ citizens/residents injured between 2007–2009. Of the 2856 POIS participants, 677 reported being migrants (i.e. born outside NZ). Data about pre-injury and injury-related potential risk factors were collected from interviews and electronic injury data. Disability outcomes were assessed with the World Health Organization Disability Assessment Schedule (WHODAS II 12-item); dichotomised into 'No/Lesser' (<10) or 'Considerable' disability (≥10). Results: Twelve years post-injury, 1497 participants reported WHODAS outcomes, including 301 (20%) migrants. Among migrants 16% (n=49) reported considerable disability. After adjusting for other predictors in the multivariable model, migrants who: 1) perceived a threat to their life when injured (aRR=3.27; 95%CI 1.22–7.83), or 2) had an inadequate household income (aRR=1.84; 95%CI 0.95–3.59), were at increased risk of disability 12-years post injury. Hospitalisation lowered the risk (aRR=0.18; 95%CI 0.04–0.55). Conclusions: The proportion of migrants disabled 12-years post-injury (16%), while lower than found 3-months post-injury (45%), it is markedly higher than pre-injury (4%). Reducing longer-term disability is required. Learning outcomes: To reduce longer-term disability among migrants, identification of those with perceived injury threat and/or inadequate household income (independent of hospitalisation) for early intervention and increased support might be beneficial.